The Impact of Applying Talent Management Strategies on Achieving Happiness in the Work Environment: An Applied Study on the Royal Jordanian Airlines Company - Al-Rawashdeh, Ayad Taha (International Review of Management and Marketing, 2021)
A questionnaire was created to collect data in order to accomplish the objectives of the analysis. The research population consisted of (1669) Royal Jordanian Airlines workers with distinct job titles. The investigator used the simple random sample method of (180) people. The Statistical Kit for Social Sciences (Spss.19) was used, and the analysis drew multiple conclusions, the most important being: the perceptions of members of the study sample of the level of talent management techniques in the researched organization are of a high level, and the perceptions of individuals of the study sample of the level of satisfaction in the work environment in the researched co-operator. The study suggests that the organizational culture within the business be initiated on the basis of talent management techniques and the crystallization of principles that express the concepts of participation and cooperation, collaboration and the diversity of skills due to their positive effect on the achievement of participation and cooperation. Keywords: talent management strategies; achieving happiness at work environment; Royal Jordanian Airlines. JEL Classifications: A10, A19 DOI: https://doi.org/10.32479/irmm.10923